Biotechnological and pharmacological assessment of pyocyanin from marine Pseudomonas otitidis EGY-NIOF-A1 as an antimicrobial agent against clinical pathogens - Hatem M. Abuohashish; Amany S. El Sharkawy (Current Research in Biotechnology, 2023)
Background: The marine ecosystem is rich in a wide diversity of microorganisms that represent a source of therapeutically effective bioactive chemicals. Objectives: This study aims to isolate a phenazine-related compound from a marine pseudomonas strain and to evaluate its antimicrobial effects against health-related pathogens. Methods: The 16S rRNA of the marine isolated bacteria was compared with the gene sequences in the GenBank database. In addition, the antimicrobial sensitivity of the marine isolate was tested using VITEK 2 system. A phylogenetic tree was constructed, and the nucleotide sequence was submitted to the GenBank database. The phenazine-related compound was extracted and purified from the marine isolate, and characterized by reverse-phase HPLC, FTIR, and UV–Vis. Then, its antimicrobial activity was assessed against eight health-related pathogens. Results: The phylogenetic and 16S rRNA gene analysis revealed that the marine isolate was Pseudomonas otitidis, with antimicrobial resistance against cefazolin and imipenem. The purified phenazine molecule was identified as pyocyanin with a distinctive blue color. The pyocyanin was characterized by reverse-phase HPLC analysis at 313 nm. FTIR analysis showed multiple peaks indicating pyocyanin functional chemical groups. UV–Vis also characterized pyocyanin at 385 nm. The marine-derived pyocyanin demonstrated antimicrobial effects against Streptococcus pneumoniae, Staphylococcus aureus, and Enterococcus faecalis, while resistance effects against the remaining pathogens. Conclusion: Taken together, this is the first record to purify the characteristic blue pyocyanin from a species other than P. aeruginosa. The marine-isolated P. otitidis represents a new promising source of a novel marine-derived pyocyanin, which has antimicrobial efficacy mainly against Gram-positive pathogens.